Stable sealing glass for planar solid oxide fuel cell - Sohn, SB; Choi, SY; Kim, GH; Song, HS; Kim, GD (ELSEVIER SCIENCE BV, 2002)
The thermal and chemical stability of glasses in the BaO-Al(2)O(3)-La(2)O(3)-B(2)O(3)-SiO(2) system were investigated as well as bonding characteristics and wetting behavior to yttria stabilized zirconia (YSZ) electrolyte, to develop a suitable sealing glass for planar solid oxide fuel cell operating at 800-850 degreesC. The thermal properties such as glass transition temperature, softening temperature and thermal expansion coefficient were found to depend on the B(2)O(3):SiO(2) ratio in glass composition; thus the bonding characteristics of the glass to YSZ were also influenced by this ratio. The glass having a minimum thermal expansion mismatch with YSZ showed an excellent endurance during thermal cycling. No interface reaction was observed for all the glass/YSZ specimens heat-treated at 800-850 degreesC up to 100 h. (C) 2002 Elsevier Science B.V. All rights reserved.